(untitled) (Tribhuvan University Journal of Microbiology, 2018)
Objectives: The study was done to assess liver function test among hepatitis B surface antigen (HBsAg) positive blood donors. Methods: Liver function test (LFT) were studied in 71 HBsAg positive serum samples from healthy blood donors. Results: In the study, 14(19.7Ü) serum samples showed elevated alanine aminotransferase (ALT) level above the normal range (5_35 IU/I) with mean 66.3±27.6; 16(22.5%) showed aspartate aminotransferase (AST) level above the normal range (5-40 IU/I) with mean 87.5±35.7; 4(5.6%) serum samples showed alkaline phosphatase (ALP) level above the normal range (306 IU/I) with mean 376.5±31.5; 49(69%) samples were found to be below the normal albumin level (38-51gm/I) with mean 23.9±5.76. Conclusion: Deviations in the serum enzymes (ALT, AST and ALP) as well as total protein and albumin level showed the silent infection of hepatitis B virus in healthy blood donors.